2014
DOI: 10.1007/s12541-014-0558-8
|View full text |Cite
|
Sign up to set email alerts
|

Erratum to: Guidelines for tilt measurements realized by MEMS accelerometers

Abstract: The paper discusses thoroughly a problem of determining tilt over various measurement ranges by measuring Cartesian components of the gravity acceleration with application of accelerometers that are Microelectromechanical Systems (MEMS). The presented standard and original methods are based on various mathematical relationships between the components and the pitch and the roll. Their application results in the fact that the realized measurements are characterized by different sensitivity and accuracy (experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…However, assuming such repeatable calibration, it must not be forgotten that alignment precision, being a crucial issue pertaining to application of MEMS accelerometers, especially with respect to their calibration accuracy [47], may be also a subject to aging processes. Alignment precision is a matter of great importance in the case of determining tilt angles [48], especially while striving for high accuracy of the measurements [49], as proved e.g. by result of experimental studies reported in [50].…”
Section: Discussionmentioning
confidence: 99%
“…However, assuming such repeatable calibration, it must not be forgotten that alignment precision, being a crucial issue pertaining to application of MEMS accelerometers, especially with respect to their calibration accuracy [47], may be also a subject to aging processes. Alignment precision is a matter of great importance in the case of determining tilt angles [48], especially while striving for high accuracy of the measurements [49], as proved e.g. by result of experimental studies reported in [50].…”
Section: Discussionmentioning
confidence: 99%
“…Using data of the most sensitive element at any position, an accurate measurement of tilt in the whole range will be achieved accordingly. Łuczak gave the concept of tilt measurement systems utilizing multi-axial accelerometers [ 18 ], and disscussed application of arc tangent function, which can also ensure a constant sensitivity of tilt measurement [ 19 ]. Enfu Li et al achieved a tilt sensor with a high resolution maintained in the full measurement range based on one dual-axis micro-accelerometer [ 20 ].…”
Section: Sensing Principle and Structure Designmentioning
confidence: 99%
“…They are also successful sensors for various environmental monitoring uses. MEMS inclination sensors are widely used in buildings, bridges, power transmission networks, automobiles, and other engineering vehicles [ 1 , 2 ]. Accelerometers with high performance and high reliability have great market value.…”
Section: Introductionmentioning
confidence: 99%